PENGEMBANGAN FILM DOKUMENTER SUKU KAJANG SEBAGAI MEDIA PEMBELAJARAN KEARIFAN LOKAL MATA PELAJARAN MUATAN LOKAL KELAS X SMA NEGERI 10 BULUKUMBA - Sofyan; Febriati, Farida; Citra Rosalyn Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This development research aims to: (1) Identify the need for documentary films at SMA Negeri 10 Bulukumb. (2) Designing a documentary film at SMA Negeri 10 Bulukumba. (3) What is the level of validity & practicality of documentary films at SMA Negeri 10 Bulukumba. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development method. This research was conducted at SMA Negeri 10 Bulukumba with a total of 30 students and 1 subject teacher as research subjects. The product trial was designed to consist of an alpha test carried out by 2 experts, namely a media expert who obtained an average score of very good qualifications and a content/material expert who obtained an average score of very good qualifications so that the documentary film could be tested in the field. To find out the practicality and beta test which was carried out through a small group test, the average score was found to be in the practical qualifications, while the large group test obtained an average of very practical qualifications and the results of the subject teachers' responses were in the very practical qualifications. This means that it can be stated that the Kajang Tribe documentary film as a medium for learning local wisdom is very practical to use in the learning process, especially local wisdom. This development research has resulted in a documentary film product that is suitable for use in the learning process at SMA Negeri 10 Bulukumba.